Comparison of ambulatory blood pressure and clinic blood pressure in relation to cardiovascular diseases in diabetic patients. Issue 33 (August 2017) - Shen, Jian; Li, Zhi-Ming; He, Li-Zhen; Deng, Ren-Sheng; Liu, Jing-Guang; Shen, Yuan-Sheng
Abstract : Abstract: The aim of this study was to evaluate prognostic values of ambulatory blood pressure (ABP) and clinic blood pressure (CBP) in diabetic patients with hypertension. A total of 450 diabetic hypertensive patients without established cardiovascular diseases were enrolled and 416 patients who had finished 12months' follow-up were included in final analysis. Baseline data were collected and Cox proportional hazards regression analysis was used to evaluate prognostic value of ABP and CBP. Compared to those without study endpoints (n = 370), those experienced study endpoints (n = 46) were more elderly and more likely to be male, and had longer hypertension duration (7.0 ± 3.0 years vs. 6.4 ± 2.1 years, P < .05). No significant between-group differences in CBP indices were observed. However, those with study endpoints had significantly higher 24-hour systolic BP (SBP) (134 ± 10 mmHg vs. 128 ± 7 mmHg), nighttime SBP (130 ± 7 mmHg vs. 120 ± 5 mmHg), night/day SBP ratio (0.97 ± 0.09 vs. 0.94 ± 0.08), higher proportion of non-dipping BP pattern (39.1% vs. 31.4%) and higher 24-hour SBP variability. After extensively adjusted for traditional risk factors, nondipping BP pattern and 24-hourSBP, only 24-hour SBP and nighttime SBP remained independently related with cardiovascular outcomes, with hazard ratios and associated 95% confidence interval as 1.53 (1.28–2.03) and 1.50 (1.26–1.89), respectively. Although no independent relationship between BP pattern and cardiovascular outcomes was observed. In summary, in diabetic hypertensive patients without established cardiovascular diseases, baseline 24-hour SBP and nighttime SBP are useful markers for predicting short-term cardiovascular outcomes.